Risk of Emergency Situations of Underground Objects in the Perspective of Multi-Criteria Decision Making - Dachowski R.; Gałek K. (Archives of Civil Engineering, 2019)
The diaphragm wall and the open caisson represent two main competitive technologies used in the construction of underground objects. In modern times, diaphragm walls are primarily applied for large-size objects, with open caissons being preferred in the case of small-sized ones. Currently, objects of this type are designed mainly for sewage treatment plants and detention reservoirs. Their construction involves highly labour-intensive processes. During the execution of works unforeseen negative effects are observed to occur. During the underground objects construction the most common phenomena are: deviations from the vertical (tilt), sagging, sinking below the designed level, cracking, scratches or leakage through the wall. The purpose of the paper is to classify undesired risk factors emerging in the process of underground objects construction and selection of the optimal technological and material solution for municipal facilities. The implementation of this task involved the selection of Multi-Criteria Decision Making methods, taking into account the cause-effect rating, as the mathematical apparatus. The Ratio Estimation in Magnitudes or deciBells to Rate Alternatives which are Non-DominaTed (REMBRANDT) method was applied. The research proved that it is possible to analytically assess unforeseen risk factors conducive to emergency situations during the implementation of underground objects, using the REMBRANDT method.